الضرائب غير الشرعية في دولتي المرابطين والموحدين وأثرها على علاقتهما مع الرعية - غانية, البشير (جامعة الوادي - University of Eloued, 2016)
يقوم المقال على اشكالية الضرائب الغير شرعية في مختلف مراحل دولتي المرابطين والموحدين أي منذ القيام إلى السقوط، وأثرها على طبيعة علاقتهما مع الرعية. وقد وجدنا أن المرابطين قد تراجعوا عن مبدأ إلغاء الضرائب الغير الشرعية منذ بدايات حركتهم، إلا أن هذه الظاهرة تدرجت نحو التفاقم مع انتقال المرابطين من حركة دينية إلى ملك سياسي، وهذا ما انعكس على علاقة الدولة بالرعية، حتى أن الكثير من المؤرخين اعتبروا الضرائب الغير شرعية من أهم العوامل التي عجلت بسقوط دولة المرابطية. أما الموحدون اكتفوا بالضرائب الشرعية دون سواها، وبهذا استطاع الموحدون تجاوز مشكل الضرائب الغير شرعية رغم بعض التجاوزات لعمالهم في جمع الضرائب، لذا يمكننا أن نقر بأن النظام الضريبي الموحدي كان أكثر تنظيما من سابقه. ABSTRACT: The article on the problematic of illegal taxes at various stages of the states and stationed Unitarian do any since the fall, and its impact on the nature of their relationship with the parish. We have found that marabouts have backed the principle of the abolition of non-legitimate tax since the beginning of the movement, however, that this phenomenon gradually toward exacerbations with transmission stationed from the religious movement into a political king, and this is reflected in the country's relations with the parish, so that many historians considered illegal taxes of the most important factors that precipitated the fall of the Almoravid state. The Unitarians were satisfied with the taxes legitimacy without the other, and thus was able to overcome the Unitarians illegal tax problem, despite some abuses of workers in the collection of taxes, so that we can recognize that the tax system Almohad was more organized .than its predecessor.
مقال
Keywords: الضرائب غير الشرعية - المرابطين - الموحدين